NANOPARTÍCULAS LIPÍDICAS SÓLIDAS DE PALMITATO DE METILA PARA CARREAMENTO DA CURCUMINA - Lopes, Vanessa Falchetti (2021)
Solid lipid nanoparticles are considered a promising way for compounds encapsulation that show physical and chemical limitations, such as curcumin, which despite exhibiting several therapeutic applications, has a lower bioavailability after an oral administration and low solubility in physiological solutions. Therefore, the use of pharmaceutical nanotechnology as a tool to expand the physical-chemical properties of curcumin stands out. Methyl palmitate is an ethanol soluble lipid and endogenous from the metabolism, however, not yet used to obtain nanostructured systems. Thus, the goal of this study was to obtain, characterize and perform biological evaluation assays of solid lipid nanoparticles of methyl palmitate with curcumin in it. For this, a factorial design was used in order to optimize the conditions of obtaining the developed nanoparticles by the high shear homogenization method. As a result, the nanoparticles which contain curcumin presented: average diameter of 162.41 ± 5.7 nm with monomodal distribution profile; 0.10 ± 0.05 poly-dispersion index, characterizing homogeneity of the suspended particles; zeta potential of -18.00 ± 0.2 mV and 68.42% ± 0.7 of encapsulation efficiency. After the lyophilization process with mannitol (5%), the nanoparticles presented at the end of 150 days, 261.63 ± 8.75 nm, polydispersion index of 0.25 ± 0.03 and zeta potential – 19.45 ± 0.78 mV, suggesting the use of mannitol for a cryoprotection and stability of the system during storage. In addition, the nanostructured system presented, through the X ray diffraction technique, lower crystallinity index value in relation to isolated methyl curcumin and methyl palmitate and, according to the infrared spectrograms, there was no chemical interaction that could modify the characterized functional groups. The results of the thermal analysis showed that curcumin was dispersed amorphaly in the nanoparticles and the microscopy images confirmed the nanometric size. In the in vitro assays, the nanoparticles showed stability when submitted to simulated gastrointestinal fluids, protecting the molecule from pH variations and in phosphate buffer saline (PBS), 60% of the curcumin was released through the lipid matrix. The applicability of the nanoparticles was evaluated by the potential antioxidant study, and also by evaluating cytotoxicity in erythrocytes and Candida sp. Regarding the antioxidant study, the nanostructured system demonstrated a similar inhibition to free curcumin against Acid2,2'-azinobis-3-ethylbenzothiazolin-6-sulphonic (ABTS●+). Cytotoxicity on erythrocytes was higher with free curcumin than with the nano-encapsulated. The anti-fungal activity of the nanoparticles was dose-dependent, with minimal inhibitory concentration (MIC50) at 7.5 μg.mL-1 under all tested strains. In the pharmacokinetic assay, a significant improvement was observed in the pharmacokinetic parameters of curcumin when nano-encapsulated to, after oral single-dose administration in mice. The amount of curcumin available in plasma was higher when transmitted in the nanoparticles (AUC0-t = 117.85 ± 10,63 ng.h/mL-1) compared to the free molecule (AUC0-t = 34.36 ± 13,76 ng.h/mL-1) and the bioavailability of curcumin in the nanoparticles was three times higher than that presented by the free molecule. Finally, the results of this unprecedented study indicate that methyl palmitate can be used in the development and application of oral lipid nanoparticles, and that the system has the potential to improve curcumin bioavailability.